Creating a Godless Community: The Collective Identity Work of Contemporary American Atheists. Issue 1 (1st March 2013) - Smith, Jesse M.
<x xml:space="preserve">Abstract</x> Based on 45 in‐depth interviews, textual analysis, and participant observation with seven different atheist organizations, this article investigates the collective identity work of atheists in the United States. It explores the social psychological and interactional dynamics of atheist organizations as well as how they contribute to the construction and maintenance of atheist identities. I discuss the various strategies atheists employ as they collectively manage a stigmatized identity and negotiate the meaning of their atheism with one another and with the nonatheist public. This is accomplished in part through an analysis of the identity politics and minority discourse contemporary atheists currently engage. In addition, and more broadly, this study explores the relationship between collective identity and social action through an analysis and description of contemporary atheist activism.